Implementation of the Bengkulu City Government’s Obligations Regarding the Provision of Temporary Waste Collection Sites (TPS) Under Law No. 18 of 2008 on Waste Management - Muhammad Bintang Ramadhan; Sukirman Adi Wijaya; Satria Hidayat; Desi Hafizah (The Future of Education Journal, 2026)
This study examines the implementation of the Bengkulu City Government’s obligation regarding the provision of Temporary Waste Collection Sites (TPS) in accordance with Law No. 18 of 2008 on Waste Management and other relevant regulations, focusing on the Bengkulu City area. This study is a normative-empirical legal study that analyzes the gap between legal norms (das sollen) and actual practices in the field (das sein). The main issue examined is the lack of TPS provision in Bengkulu City, which encourages the public to frequently dispose of waste indiscriminately and to designate certain locations as illegal TPS that do not meet technical requirements. This study employs a statutory approach and a conceptual approach, utilizing data collection techniques through literature review and field research. The results of the study indicate that the implementation of waste collection points in several areas of Bengkulu City has not been optimal and has not fulfilled legal obligations as mandated by Law No. 18 of 2008 on Waste Management, as well as the provisions in Bengkulu City Regional Spatial Planning Regulation (RTRW) No. 4 of 2021, specifically regarding the ideal ratio of waste collection points per sub-district.